Optimizing Biology Education: Unpacking Influence of Class Size and School Environment on Student Performance - Afeez Tunde Jinadu; Kabirat Adesola Aderemi (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
The study determined the influence of school environment and class size on senior secondary school students' biology performance in Ibadan North Local Government, Oyo State. Descriptive research design was adopted. All SS2 students in Ibadan North Local Government formed the population with a sample of 100 SS2 biology students randomly selected from public secondary schools in Ibadan North Local Government. Class Size Questionnaire-CSQ (r=0.95), School Environment Questionnaire-SEQ (r = 0.72), and Biology Achievement Test-BAT (K-R_20=0.76) were used to collect data. Data collected were analysed using multiple regression. A linear relationship was found between the independent variables (class size and school environment) and students' biology achievement in Ibadan North Local Government secondary schools. Class size and school environment jointly accounted for 71.1% of the variance in biology achievement among secondary school students in Ibadan North Local Government, with significance at F(2,97)= 4.785 p < 0.01. Class size and school environment significantly influence student achievement in biology within Ibadan North Local Government Area, Oyo State. Therefore, authorities should implement the teacher-student ratio policy to reduce classroom overcrowding and government should invest more in education by increasing the facilities in schools to create a conducive learning environment for improve academic performance in biology as well as other school subjects.